1994
DOI: 10.1161/01.cir.89.2.799
|View full text |Cite
|
Sign up to set email alerts
|

Induction of myocardial insulin-like growth factor-I gene expression in left ventricular hypertrophy.

Abstract: Background Left ventricular hypertrophy is a generalized adaptation to increased afterload, but the growth factors mediating this response have not been identified. To explore whether the hypertrophic response was associated with changes in local insulin-like growth factor-I (IGF-I) gene regulation, we examined the induction of the cardiac IGF-I gene in three models of systolic hypertension and resultant hypertrophy.Methods and Results The model systems were suprarenal aortic constriction, uninephrectomized sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
65
2

Year Published

1997
1997
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(73 citation statements)
references
References 55 publications
6
65
2
Order By: Relevance
“…Addition of IGF-I to cultured newborn rat cardiocytes stimulates the expression of muscle-specific genes that induce myocyte hypertrophy (28). In addition, there is sufficient evidence showing that IGF-I mRNA and protein increase in parallel with the development of cardiac hypertrophy (9). Furthermore, in the volume-overload model we have shown that cardiac myofibers have an increased receptor affinity to IGF-I, which corroborated with the induction of eccentric hypertrophy (20).…”
supporting
confidence: 64%
“…Addition of IGF-I to cultured newborn rat cardiocytes stimulates the expression of muscle-specific genes that induce myocyte hypertrophy (28). In addition, there is sufficient evidence showing that IGF-I mRNA and protein increase in parallel with the development of cardiac hypertrophy (9). Furthermore, in the volume-overload model we have shown that cardiac myofibers have an increased receptor affinity to IGF-I, which corroborated with the induction of eccentric hypertrophy (20).…”
supporting
confidence: 64%
“…In cultured neonatal cardiac myocytes, IGF-I induces an early and sustained expression of the muscle-specific genes for troponin I and myosin light chain-2 with myocyte size almost doubling after 48 h of treatment with IGF-I (14). An increase in left ventricular IGF-I mRNA and its protein has been described in pressure overload cardiac hypertrophy in various models of hypertension; this suggests that IGF-I may be an important mediator of an adaptive hypertrophic response (21,45,46). However, the results of overexpression of IGF-I in transgenic mice have been contradictory (22,47).…”
Section: Discussionmentioning
confidence: 98%
“…Increased plasma IGF-I concentrations have been reported in patients with hypertension and cardiac hypertrophy (20). The hypertension induces significant increases in cardiac IGF-I mRNA and protein in parallel with the onset and early development of experimental cardiac hypertrophy; this is followed by a normalization of the IGF-I mRNA once the hypertrophic response is established (21). A very recent report has established that the overexpression of IGF-I in cardiac myocytes leads to cardiomegaly mediated by an increased number of cells in the heart (22).…”
mentioning
confidence: 99%
“…22 Changes of this nature, such as increased expression of the beta-myosin heavy chain mRNA and insulin-like growth factor production, are similar to those seen in human cardiomyocytes with pressure overload induced hypertrophy in vivo. 23,24 The pathological remodelling of the ventricle occurring in pressure overload is not however simply caused by increases in myocyte size, but also involves a progressive interstitial fibrosis. Angiotensin II binding to the AT 1 receptor has also been shown to be responsible for a significant increase in collagen synthesis by cardiac fibroblasts.…”
Section: Left Ventricular Hypertrophymentioning
confidence: 99%